Step-by-step explanation:
Hey there!
The given points are; (4,4) and (1,2) as (x1,y1) and (x2,y2).
Note: Use double point formula for the equation.
Now;
[tex](y - y1) = \frac{y2 - y1}{x2 - x1} (x - x1)[/tex]
Put all values.
[tex](y - 4) = \frac{2 - 4}{1 - 4} (x - 4)[/tex]
Simplify it.
[tex](y - 4) = \frac{ - 2}{ - 3} (x - 4)[/tex]
[tex](y - 4) = \frac{2}{3} (x - 4)[/tex]
[tex](y - 4) = \frac{2}{3} x - \frac{2}{3} \times 4[/tex]
[tex]y = \frac{2}{3}x - \frac{8}{3} + 4 [/tex]
[tex]y = \frac{2}{3} x - \frac{8 + 12}{3} [/tex]
[tex]y = \frac{2}{3} x + \frac{4}{3} [/tex]
Therefore, the equation is; y = 2/3x+4/3.
Hope it helps...